1997
DOI: 10.1017/s0022377897005837
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic modulational Alfvénic turbulence

Abstract: The nonlinear dynamics of a finite-amplitude Alfvén wave in a dispersive modulational regime is analysed. Use is made of a conservative model to show that turbulence may arise via deterministic chaos. The behaviour of the system is studied as one varies the initial amplitude of the pump Alfvén wave, the dispersion parameter and the plasma parameter β.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…In the next section, the model (23)(24) is used to investigate two parametric instabilities extensively studied in classical plasmas: the decay instability and the four-wave interaction.…”
Section: Quantum Zakharov Equationsmentioning
confidence: 99%
“…In the next section, the model (23)(24) is used to investigate two parametric instabilities extensively studied in classical plasmas: the decay instability and the four-wave interaction.…”
Section: Quantum Zakharov Equationsmentioning
confidence: 99%
“…A numerical study of acceleration of Alfvén solitons by Nocera and Buti [1996] based on DNLS shows that under the action of an external harmonic driver nonlinear wave interactions develop and evolve to spatiotemporal chaos. De Oliveira et al [1997] studied Alfvén spatiotemporal chaos in a dispersive modulational regime by solving a set of coupled wave equations. Buti [1999] discussed spatiotemporal chaos in nonlinear Alfvén waves described by DNLS.…”
Section: Alfvén Chaosmentioning
confidence: 99%
“… Buti et al [1999] showed that inhomogeneities can destroy the integrability of an Alfvén system, inducing chaos even without any driver. de Oliveira et al [1997] used the spectral method to solve a set of nonlinearly coupled MHD wave equations. Their results showed that the degree of Alfvén chaos is a function of wave amplitude, plasma β , and the dispersive parameter.…”
Section: Introductionmentioning
confidence: 99%